Clinical Ethics and the Necessity of Stories Essays in Honor of Richard M. Zaner - Wiggins, Osborne P.; Allen, Annette C.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2011)
This collection of articles honors the work of Richard Zaner, a distinguished philosopher who has worked for over twenty years as an ethics consultant at Vanderbilt University Medical Center. His work in the clinical setting, especially the use of narrative in understanding what is going on in this setting, is the focus of some of the papers. Others relate his methodology and phenomenological approach to the more standard bioethical problems and approaches. The essential questions: What is the role of the phenomenological philosopher turned medical ethicist? Is medical ethics a form of applied philosophy, or is it also a form of therapy? What kind of (3z(Bethics(3y (Bemerges from a careful narrative rendering of clinical situations?s
Keywords: Medicine; Medical ethics; Medicine & Public Health; Theory of Medicine/Bioethics.